Bibliography of the Journal Materinski list (1901–1903) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The journal Materinski list: an illustrated monthly magazine for home care and nurturing of children, examination of childhood and work in kindergarten was launched in 1901, and was published uninterruptedly once a month (except for several double issues) from January 1901 until December 1903. Different editors took turns in running the journal – from No. 1 (1903) it was edited by Raša Mitrović, Miladin P. Ljujić, and Milisav D. Marković; from No. 4 (1903) its editors were Raša Mitrović and Miladin P. Ljujić. Numbers 11/12 (1901) and 11/12 (1902) included annual contents; the 1903 volume also contained a list of associates which, in processing bibliographical items, contributed to interpreting the authors’ initials. It is important to mention that the journal, though launched by teacher Raša Mitrović, assembled intellectuals with different educational backgrounds, of both male and female gender. In order to facilitate searching and simplify usage, the bibliography has been also equipped with accompanying registers which single out the title and author from the bibliographical description.
Keywords: Materinski list; periodical; bibliography; education; childhood